[After the Aguilar wedding ceremony] - Esther Aguilar::::::photographer::: (2005)
Description supplied by photographer: 'Francisco Javier y Guadalupe Aguilar celebrando su boda el 3 de Enero del 2005. Despúes de la ceremonia van en camino a la recepción para celebrar con la familia y amigos.' Translation of description: 'Francisco Javier and Guadalupe Aguilar after their wedding ceremony on January 3, 2005. They are on their way to their reception with to celebrate with family and friends.'